AUTHENTIC HAPPINESS IN RAISSA ALMIRA'S ROMANCE POETRY: A POSITIVE PSYCHOLOGY STUDY MARTIN SELIGMAN’S PERSPECTIVE: AUTHENTIC HAPPINESS DALAM PUISI ROMANSA RAISSA ALMIRA : KAJIAN PSIKOLOGI POSITIF PERSPEKTIF MARTIN SELIGMAN - Maulana Muhammad Fikri; Abdul Muntaqim Al Anshory; Ismail Marjuki; Rayhan Hafizh Ananda (Jurnal Kata, 2024)
Positive psychology emerges as a critique ti psychology, initially focusing on mental well-being as a foundation for critiquing literary psychology. Literary psychology examines the phenomena and dynamics of human life. This study aims to reveal aspects that can serve as benchmarks of happiness and assess their essence compared to the meaning of poetry. The research objects are Raissa Almira's romantic poems, analyzed using a descriptive qualitative method with a mimetic approach. Primary data sources are three of Almira's romantic poems, supplemented by secondary sources such as documents, books, and related research. Data collection techniques include reading and noting, while data analysis employs interpretation techniques to analyze the meaning of the poems and then compare it with the applied theory. The results indicate the presence of numerous negative emotions in the meanings contained in it. Through Martin Seligman's happiness framework, it is demonstrated that aspects of happiness can be found even in the expression of sad emotions through poetry. Literary criticism reveals both strengths and weaknesses in the content of these poems, despite their complex language. However, this research identifies dimensions of happiness and the essence of the meanings of the poems, serving as benchmarks for an individual's personality within a diverse society.